Benchmarking methods and data for the whole-outline geometric morphometric analysis of lithic tools - Araujo, Renata P. (2023)
Originally developed for the quantitative analysis of organismal shapes, both two-dimensional (2D) and 3D geometric morphometric methods (GMMs) have recently gained some prominence in archaeology for the analysis of stone tools1-3—unquestionably the primary deep-time data source for the earliest periods of human cultural evolution.4 The key strength of GMM rests in its ability to statistically quantify and hence qualify complex shapes, which in turn can be used to infer social interaction,5 function,6, 7 reduction,8 as well as to assess classification systems and cultural relatedness.